GERENCIA DE RECURSOS HUMANOS EN LOS PROYECTOS APLICACIÓN DEL PRINCIPIO DE LA CARGA VERTICAL EN EL TRABAJO PARA EL DESARROLLO DEL EQUIPO DEL PROYECTO - Bravo Salomóna, Luis Humberto (2019)
Within the areas of the knowledge of the PMI one is the Management of the Human Resources, the same that is in charge of the processes that organize and direct the project team, the same that is made up of people with rolls and assigned responsibilities to conclude the project. Considering that is necessary to count on personnel involved and identified with the project, it is necessary to know some technique to apply to achieve that objective. Psychologist Frederick Herzberg indicates that three general philosophies of the personnel administration exist. First one is based on the organizational theory, second in industrial engineering, and third in the science of the conduct. Within this last philosophy, Herzberg he raises what it denominates “Principles of the Vertical Load of Work”, indicating that this consists of employing to motivating factors when assigning. For it he determines seven principles associate that them, each of them, to “types” of motivating, denominate that them motivating implied. In this way he obtains what the flame “Labor Enrichment”. This theory appears, the same that has been applied of experimental way obtaining satisfactory results.